The Reception of the Concept of Embodiment in Architectural Phenomenology - Petrushikhina, Svetlana V. (Actual Problems of Theory and History of Art, 2022)
This article is devoted to the question of corporeality within the phenomenology of architecture. It aims to observe how this term is represented in theoretical works by architects and theorists, such as Alberto Perez-Gomez, Juhani Pallasmaa, and Steven Holl. These theorists are concerned about the social and cultural context of architecture. Furthermore, they pointed out the importance of sensory perception as a key factor in the process of interaction between a building and its user. They believed that pure, genuine contact could only be achieved at the pre-speculative level. They argue that the body does not exist separately from the surrounding space, as well as the space is inextricably linked with its viewer. An experience received by the body through its senses turns into one holistic image. The qualitative characteristics of space — such as length, width, color, depth — are determined solely by the senses, that is, through the body. Thus, the theorists of phenomenological movement emphasize the value of embodiment both in the design and the perception of architecture.